Perancangan Interior Inkubator Bisnis Kuliner Di Kota Tasikmalaya Dengan Pendekatan Visual Merchandising - Zashika Rizki, Salsabila; Sarihati, Titihan; Adli Wismoyo, Erlana (KalaTanda, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia’s economy, especially in TasikmalayaCity, which has seen rapid growth in culinary MSMEs with 1,056 businesses. However, there remains a lack of adequatephysical facilities to support these MSMEs’ potential. This study focuses on developing the interior of a culinary businessincubator to address issues such as layout affecting consumer purchasing power, inadequate facilities according to businessincubator standards, and hygiene concerns. The research methodology employed qualitative descriptive methods involvingliterature review, interviews, field observations, and benchmarking studies. The analysis results advocate for visual merchandising as a solution to enhance the marketing of culinary MSME products and create a positive and efficient spatialexperience. The goal of this design is to tackle identified local challenges, aiming for the incubator to improve marketingfor culinary MSME products, foster business growth, and provide facilities that support operational efficiency and productinnovation. The study concludes that implementing visual merchandising based on specified parameters can create interiordesigns that capture attention and enhance consumer experiences. The benefits include creating positive experiences thatinfluence consumer purchasing behavior and enhance customer loyalty, ultimately fostering local economic development,increasing national income through MSME contributions, and facilitating culinary entrepreneurs in enhancing the quality oftheir products and services.